Risco e taxa de retorno: agroindústria cooperativa versus pequena propriedade rural - Bastiani, Ivoneti C. Rigão (1992)
This thesis analysed the relationship between risk and rate of return from agroindustry cooperative and small home farm (whose farmers are affiliated to the former). The model applied is based on Markowitz. The analysis embodies: a) risk and return got by the two groups of economical entities, as well as by the main farming; b) economical benefits for the agroindustry cooperative to small home farm by reason of the horizontal/vertical diversification strategics adopted by the former; c) agricultural production decisions with regard to specialization or diversification strategies in small home farm; and d) the applicability of risk diversification models commended by the financial portfolio theory in the small home farm’s agricultural production, considerate Markowitz model compared to MOTAD linearization process. The results showed that there was an expressive raise in both cooperatives everage rate of returns, due mainly to the industrialization of the products. And the power of returns produces is meaningly higher in this corporation than the small home farm. The risk levels are also distinguished. In relation to the agricultural production diversification this didn’t result in a decrease of returns variability. The likely reason for this result is linked to production portfolio composition. Considering the utilization of Markowitz and Hazell models to the choice of an optimum farm plan under risk, these are effective in despite of a set of operational difficulties and they don’t assure the solution of all the risk management problems. As a matter of fact these models consist in one more instrument which the farmer can use in the agricultural production risk management.